Lumpang: Subjek dalam Masyarakat Homogen (Studi di Desa Torongrejo, Kota Batu, Jawa Timur) - Muhammad Hayat (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
The phenomenon of lumpang as one of the points of view in the idea of culture as the basis for people's actions shows that lumpang is not just a symbol that is only literally accentuated. Instead, what appears is a symbol of the practice of community social values. Symbols in sociology are not merely things that have no life in their relationships. The approach used is qualitative through the depth of interview (interpretative understanding). The analysis used is the analysis model from Miles and Hubermen, which rotates like a cycle, namely data collection, data reduction, data presentation, and drawing conclusion. The result showed that lumpang is the basis for community economic knowledge and lumpang is a culture that remains as the subject. The conclusion of this research is that lumpang as a subject in a homogeneous society is the subject is good manners, the subject is awareness to respect others, the subject is awareness to protect, and the subject is submission. The four things symbolized by lumpang are important links in the way people understand nature. There is space to use without having to eliminate traces of nature. This is a subject that realizes not the given subject.